<h3>Answer: A. 5/12, 25/12</h3>
============================
Work Shown:
12*sin(2pi/5*x)+10 = 16
12*sin(2pi/5*x) = 16-10
12*sin(2pi/5*x) = 6
sin(2pi/5*x) = 6/12
sin(2pi/5*x) = 0.5
2pi/5*x = arcsin(0.5)
2pi/5*x = pi/6+2pi*n or 2pi/5*x = 5pi/6+2pi*n
2/5*x = 1/6+2*n or 2/5*x = 5/6+2*n
x = (5/2)*(1/6+2*n) or x = (5/2)*(5/6+2*n)
x = 5/12+5n or x = 25/12+5n
these equations form the set of all solutions. The n is any integer.
--------
The two smallest positive solutions occur when n = 0, so,
x = 5/12+5n or x = 25/12+5n
x = 5/12+5*0 or x = 25/12+5*0
x = 5/12 or x = 25/12
--------
Plugging either x value into the expression 12*sin(2pi/5*x)+10 should yield 16, which would confirm the two answers.
Answer:
(x + 1)² = 7
Step-by-step explanation:
Given:
-2x = x² - 6
We'll start by rearranging it to solve for zero:
x² + 2x - 6 = 0
The first term is already a perfect square so that's fine. Normally, if that term had a non-square coefficient, you would need to multiply all terms a value that would change that constant to a perfect square.
Because it's already square (1), we can simply move to the next step, separating the -6 into a value that can be doubled to give us the 2, the coefficient of the second term. That value will of course be 1, giving us:
x² + 2x + 1 - 1 - 6 = 0
Now can group our perfect square on the left and our constants on the right:
x² + 2x + 1 - 7= 0
x² + 2x + 1 = 7
(x + 1)² = 7
To check our answer, we can solve for x:
x + 1 = ± √7
x = -1 ± √7
x ≈ 1.65, -3.65
Let's try one of those in the original equation:
-2x = x² - 6
-2(1.65) = 1.65² - 6
- 3.3 = 2.72 - 6
-3.3 = -3.28
Good. Given our rounding that difference of 2/100 is acceptable, so the answer is correct.
Answer:
12.5h
Step-by-step explanation:
12.5 hr x h $/hr = $12.5h
Answer:
The equation that represents the number of persons buying the phone and the price of the phone is y = -0.75·x + 60
Step-by-step explanation:
The given data are as follows
x, p($)
10, 52.5
25, 41.25
40, 30
60, 15
We note that a plot of the given points give a straight line graph indicating a linear relationship
The rate of change of p($) with x is given by slope, m in the following relation;
![Slope, \, m =\dfrac{y_{2}-y_{1}}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=Slope%2C%20%5C%2C%20m%20%3D%5Cdfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
Which gives;
![Slope, \, m =\dfrac{41.25-52.5}{25-10} = \dfrac{30-41.25}{40-25} = \dfrac{15-30}{40-60} =-0.75](https://tex.z-dn.net/?f=Slope%2C%20%5C%2C%20m%20%3D%5Cdfrac%7B41.25-52.5%7D%7B25-10%7D%20%3D%20%5Cdfrac%7B30-41.25%7D%7B40-25%7D%20%3D%20%5Cdfrac%7B15-30%7D%7B40-60%7D%20%3D-0.75)
Therefore, to write the equation in slope and intercept form, we have;
From the first point with coordinates (52.5, 10), we have
y - 52.5 = -0.75×(x - 10)
y = -0.75·x + 7.5 + 52.5 = -0.75·x + 60
The equation that represents the number of persons buying the phone and the price of the phone is y = -0.75·x + 60.